The Channel Compressive Sensing Estimation for Power Line Based on OMP Algorithm. (23rd April 2017) - Zhang, Yiying; Liang, Kun; He, Yeshen; Wu, Yannian; Hu, Xin; Sun, Lili
Abstract : Power line communication (PLC) can collect information by power line which increases the coverage and connectivity of the smart grid. In this paper, we analyze the transmission characteristics of the power line channel and model it with mathematics channel. The multipath effect of the power line channel is studied with a novel technology named compressive sensing herein. We also proposed a new method to the power line channel estimation based on compressive sensing. We can collect and extract the effective parameters of the power line channel to storage, which only take very little storage space. The simulation results show that the proposed approach can reduce the amount of processing data in the digital signal processing module and decrease the requirement for the hardware.